Frictional Behavior and Mechanical Performance of Al Reinforced with SiC via Novel Flake Powder Metallurgy - Nabeel H. Alharthi; Saud M. Almotairy; Abdulrahman M. Almutairi (Metals, 2022)
This paper targets developing new low-cost sustainable materials. To achieve this objective, aluminum was utilized as base material for metal matrix nanocomposites (MMNC). Three routes of advanced manufacturing techniques were designed and implemented. Flake powder metallurgy as a reliable method to synthesis nanocomposites powder was employed. By reinforcing aluminium with SiC and using a similar amount of both constitutes, three metal matrix nanocomposites (MMNCs) with different properties were produced. The ball milled powder were characterized using filed emission scanning electron microscope (FE-SEM) to analyze the morphology of the powder. Different investigations and analysis were conducted on the produced samples. These include X-ray diffraction (XRD) analysis, density and porosity, mechanical properties, and frictional performance. The obtained results include relative density, Young’s modulus, compressive yield strength, elongation, toughness, hardness, coefficient of friction, and specific wear rate. Achieving superior mechanical and tribological performance is evident from these results. This is accredited to the homogeneity of the reinforcement dispersion within the aluminum matrix.